5х+4=х+12 5х +(3х-7)=9 3у-(5-у)=11 (7а+1) - (6а+3)=5
5х-х=12-4 5х+3х=9+7 3у-5+у=11 7а+1-6а-3=5
4х=8 8х=16 4у=11+5=16 а=5+3-1
х=2 х=2 у=16:4=4 а=7
13-5у=8-2у (8s+11)-13=9s-5 (5х-3)+(7х-4)=8-(15-11х)
-5у+2у=8-13 8s-9s=-5+13-11 5х-3+7х-4=8-15+11х
-3у=-5 -s=-3 5х+7х-11х=8-15+4+3
у=5:3 s=3 х=0
у=1 2/3
(7-5к)-(8-4к)+5к+6=8 2х+5=2(х+1)+11 15(v+2)-30=15v
7-5к-8+4к+5к+6=8 2х+5=2х+2+11 15v+30-30=15v
4к=8-6+8-7 2х-2х = 11+2-5 15v-15v=30-30
4к=3 0х=8 0v=0
к=3/4 х≠
5(3x+1,2)+х=6,8
15х+6+х=6,8
16х=6,8-6
16х=0,8
х=0,8:16=0,05